PENGARUH ENTREPRENEURIAL ORIENTATION DAN MARKET ORIENTATION TERHADAP KINERJA UKM INDUSTRI PENGOLAHAN KELAPA SAWIT DI PROVINSI RIAU MELALUI INOVASI SEBAGAI VARIABEL MEDIASI - Putri, Hidayatna; Sari, Ria Nelly; Ratnawati, Vince (Jurnal Akuntansi (Media Riset Akuntansi & Keuangan), 2019)
The main objective of this study is to examine the general pattern of the relationship between the concept of entrepreneurial orientation, market orientation, innovation, and organizational performance in small and medium enterprise. It analyzes the mediating effects of innovation within the context of entrepreneurial firm’s palm oil in Riau, an emerging economy. This study empirically analyzes the impact of strategic orientation on firm performance through innovation with sample of 179 SMEs’s palm oil in Riau. To test the proposed model, Warp PLS 6.0 is used. The result shows that entrepreneurial and market orientation impacts performance directly and enhances firm performance through the mediation of innovation as partial mediation. The author find an interesting interplay between entrepreneurial orientation, market orientation, innovation, and organizational performance that can be very usefull to better understand how to improve firm performance. Several works have studied strategic orientation but without specifying this nature in both orientations. More recent empirically-based studies conceptualize and refer to spesific orientations. This study aims also to develop a better understanding of how entrepreneurial orientation and market orientation impacts on the performanceof SMEs and how these relationship is mediated by innovation.